The Implementation of Communicative Language Teaching (CLT) Method in English Courses at New Concept English Education Centre - Aliya Izet Begovic Yahya; Sumaryoto Sumaryoto; Hendro Prasetyono (Eduvest - Journal of Universal Studies, 2024)
This study investigates the implementation of the Communicative Language Teaching (CLT) method at New Concept English Education Centre in Indonesia, focusing on its integration with Information and Communication Technology (ICT). CLT emphasizes authentic communication and interactive pedagogy, aiming to improve students' speaking and listening skills. The research adopts a qualitative descriptive approach, utilizing in-depth interviews, classroom observations, and document analysis to assess how CLT enhances language acquisition. Findings reveal that incorporating ICT tools such as digital platforms, multimedia resources, and gamified applications significantly supports real-world communication, fostering engagement and motivation among learners. Despite these advancements, challenges persist, particularly regarding technology access and infrastructure. This study underscores the transformative potential of ICT-enhanced CLT in modern language education while offering insights for curriculum development and teacher training to optimize English language instruction in Indonesia and similar contexts.